2010
DOI: 10.1111/j.1365-2354.2008.00969.x
|View full text |Cite
|
Sign up to set email alerts
|

Alleviating existential distress of cancer patients: can relational ethics guide clinicians?

Abstract: Most people have a heightened awareness of death at the moment they receive a cancer diagnosis. Medical treatment attempts to demystify and manage death, yet surprisingly, care that alleviates existential distress is the least provided psychosocial care. A review of empirical research [quantitative and qualitative studies (n = 85) and seven literature reviews] was conducted to explore the experiences of clinicians (primarily nurses) working with cancer patients who experience existential distress. This paper s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 91 publications
2
29
0
Order By: Relevance
“…Many eventually felt they were able to explain to the clinicians what they could and could not tolerate. Although the literature suggests that patients take a passive role [18][19][20] in healthcare decision-making, this study reaffirms their wishes to more actively contribute to care decisions [6,21]. Most of the participants offered suggestions for improving the experience of cannulation.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Many eventually felt they were able to explain to the clinicians what they could and could not tolerate. Although the literature suggests that patients take a passive role [18][19][20] in healthcare decision-making, this study reaffirms their wishes to more actively contribute to care decisions [6,21]. Most of the participants offered suggestions for improving the experience of cannulation.…”
Section: Discussionsupporting
confidence: 72%
“…The aim of medical treatment, including nursing care, and the attitudes of all health professionals is to create a positive experience and outcomes for the patient. A patient's health issue can create a sense of vulnerability in regard to treatment options, leaving the patient with little choice as they perceive that some procedures just 'have to be done' [1][2][3][4][5][6]. Historically, before the advent of modern healthcare and the concept of patient-centredness, patients were often exposed to physical and/or emotional injury during the delivery of treatments-mainly as a result of lack of knowledge or skills on the part of the healthcare practitioner [7].…”
Section: Introductionmentioning
confidence: 99%
“…(McSherry and Cash, 2004;Strang et al, 2002). In a review of the literature concerning the ability of staff to alleviate existential distress, it was found that although clinicians are sometimes aware of their lack of knowing what to say and or do when patients experience existential distress, they are often aware of existential distress or spiritual meaning as being part of their work (Leung and Esplen, 2010). In order to meet patients' needs to express existential concerns, nurses have been found to develop relationships of trust through effective communication skills (Mok and Chiu, 2004;Johnston and Smith, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Survivor characteristics most related to existential concerns (for example, being female and younger) could allow supportive services provided by pastoral care or mental health professionals to be targeted to these subgroups. It is important that health care providers become aware of these concerns, even in long-term survivors, so that they may be addressed (Leung and Esplen, 2010). Although often overlooked in psychological interventions for cancer patients (Lindemalm et al, 2012), some evidence suggests that addressing existential concerns in cancer populations in general (Breitbart et al, 2012), and specifically in lymphoma survivor populations, would likely contribute to improved well-being and quality of life (Henoch and Danielson, 2009).…”
Section: Discussionmentioning
confidence: 99%